The Effect of minimum wage policy on Malaysia’s CPI & PPI: an intervention analysis - Emerzalina Emeraldi,; Siti Norafidah Mohd Ramli, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The minimum wage policy in Malaysia has been debatable due to contradicting perspectives among consumers and producers. While the consumers believe that the minimum wage policy is important to support their increasing cost of living, this policy has raised concerns among producers as they believe that this intervention might increase the cost of production, especially to producers who have been paying wages lesser than the policy’s rate. Hence it is important to numerically assess the impact of the policy on Malaysia’s consumer price index (CPI) and producer price index (PPI). To achieve this main objective, we built an intervention model using time series analysis and multiple linear regression. Based on both analyses, we conclude that only the PPI shows significant changes following the minimum wage policy implementation, whereby a decrease of 97.3% occurred in every month of 2014. However, there was no significant effect on the CPI during the first year of its establishment. Our 3 months forecast for the year 2018 also shows that the forecast of both indices is within the 95% confidence interval, which could imply that both indices are following the same fundamental structure during the 3 months period, despite the change in the Malaysian government ruling party.